REVIEW ON THE EMERGENCE OF A TRADITION: ESSAYS IN HONOR OF JESÚS HUERTA DE SOTO, EDITED BY DAVID HOWDEN AND PHILIPP BAGUS (VOL 1 MONEY AND THE MARKET PROCESS; VOL. 2 PHILOSOPHY AND POLITICAL ECONOMY). PALGRAVE MACMILLAN 2023 - , David Gordon (REVISTA PROCESOS DE MERCADO, 2024)
Jesús Huerta de Soto who is professor of economics at the Rey Juan Carlos University of Madrid is the leading representative of the Austrian school of economics in Spain. He is a renowned teacher and two of his many doctoral students David Howden and Philipp Bagus both now themselves professors of economics have edited a festschrift in his honor. The contributors include students, colleagues, friends, teachers, two of his daughters, and his son. The two-volume festschrift contains many valuable essays, but I cannot do more here than comment on a few of them, as there are no less than twenty-seven essays in the first volume and twenty-four in the second as well as two introductory essays by the editors “Jesús Huerta de Soto: A Biographical Sketch” in the first volume and “Jesús Huerta de Soto: An Appreciation” in the second.